2021
DOI: 10.1111/ijfs.15506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different agro‐industrial waste as substrates on proximate composition, metals, and mineral contents of oyster mushroom (Pleurotus ostreatus)

Abstract: The use of agro-industrial waste as substrates for mushroom cultivation is considered a promising management strategy for reducing and valorising these wastes, simultaneously reducing the cost of mushroom cultivation. In this study, oyster mushroom Pleurotus ostreatus were cultivated on twelve substrates composed of either tea waste, lime sawdust, alder sawdust, hornbeam sawdust/shaving, wheat stalk-straw, wheat bran or their composite to determine the proximate composition and accumulation of thirteen element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The values of THQ and HRI were below the specified health hazard level. Moreover, Karataş [ 45 ] also analyzed the contents of PTE in cultivated oyster mushrooms and performed THQ studies. The results revealed that the contents of six elements (Ca, Mg, Na, Zn, Cd, and Cr) were within permissible limits, indicating the edibility of the cultivated mushroom.…”
Section: Resultsmentioning
confidence: 99%
“…The values of THQ and HRI were below the specified health hazard level. Moreover, Karataş [ 45 ] also analyzed the contents of PTE in cultivated oyster mushrooms and performed THQ studies. The results revealed that the contents of six elements (Ca, Mg, Na, Zn, Cd, and Cr) were within permissible limits, indicating the edibility of the cultivated mushroom.…”
Section: Resultsmentioning
confidence: 99%
“…(2023) addressed many of these concerns by collating a number of research articles specifically relating to the importance of novel techniques and ingredients in tackling food security and sustainability issues. In part, focus in this area has been concentrated on the use of food products previously considered as waste products such as valorising plant‐based products into stable food products (Li, 2020) including pasta and breads (Bianchi et al ., 2021), and waste materials from processing practices such as the article from Karataş (2022) discussing recovery of mushroom bioactive ingredients from processing stages. In addition to this, research has also focussed on the recovery and extraction of bioactive compounds from residues from processing streams.…”
Section: Food Security and Sustainabilitymentioning
confidence: 99%
“…Tiwari and co‐workers (2021) worked on edible mushrooms analysing the potential game changer in alleviating vitamin D deficiency and improving human health. Karataş (2021) deal with the influence of different agro‐industrial wastes as substrates on proximate composition, metals and mineral contents of oyster mushroom ( Pleurotus ostreatus ), demonstrating that samples cultivated on different substrates are safe for human consumption. López‐Hortas and co‐workers (2022) performed a detailed update on the potential of bioactive compounds that can be found in edible mushrooms.…”
mentioning
confidence: 99%